In Vitro Antibacterial and Time-Kill Evaluation of the Erythrina caffra Thunb. Extract against Bacteria Associated with Diarrhoea - Olufunmiso Olusola Olajuyigbe; Anthony Jide Afolayan (The Scientific World Journal)
The antibacterial activities of stem bark ethanolic extract of Erythrina caffra Thunb. against bacteria in diarrhoea was determined in vitro by the agar diffusion and dilution, macrobroth dilution, and time-kill assay methods. The result showed that the extract produced inhibition zones ranging between  mm and  mm, and the bacteria were susceptible at concentrations ranging between ≤100 and ≤1000 μg/mL. While the MICs of the extract ranged between 39.1 and 625 μg/mL, and the MBCs ranged between 78.1 and 625 μg/mL, the MICs of Micrococcus luteus, Proteus vulgaris CSIR 0030, Enterococcus faecalis KZN, and Staphylococcus aureus OK3 were less than 100 μg/mL, and the mechanisms of antibiosis indicated that the crude ethanolic extract was highly bactericidal against the entire test bacteria isolates. In the time-kill assay, the average reduction of the viable cell count ranged between and  cfu/mL on incubating the bacteria for 4 h at the MICs, while the reduction ranged between and  cfu/mL after 8 h of incubation. Incubating the bacteria for 4 h at 2 × MICs resulted in the reduction of the viable cell count to between − and  cfu/mL, while the average reduction ranged between − and − cfu/mL after 8 h of incubation with Micrococcus luteus, Proteus vulgaris CSIR 0030, and Staphylococcus aureus OK3 being the most highly affected bacteria. The result showed that the extract exhibited broader-spectrum antibacterial activity and justifies the use of Erythrina caffra in the folkloric medicine for treating gastrointestinal infections in South Africa.